The Enhancing Maritime Emergency Response through Integrated Problem Based and Team Based Training - Fadiansyah, M Rizki; Cahyadi, Tri; Barasa, Larsen (Meteor STIP Marunda, 2025)
This study investigates the integration of Problem Based Learning (PBL) and Team Based Training (TBT) within Basic Safety Training (BST) to enhance teamwork effectiveness during simulated maritime emergencies. Conducted through a qualitative, phenomenological approach at the Sekolah Tinggi Ilmu Pelayaran (STIP) Jakarta, the research involved in-depth interviews with five trainees and two instructors, alongside direct observations. The findings demonstrate that the PBLTBT model catalyses a critical shift in trainee competence, moving from rigid procedural recall to dynamic, adaptive problem-solving. Furthermore, the methodology fostered the development of shared mental models and non-verbal coordination, building collaborative resilience under highstress scenarios. The research concludes that the synergistic application of PBL and TBT effectively bridges a critical gap in traditional maritime education by systematically developing the non-technical skills essential for modern seafaring. This evidence-based model offers a vital strategy for maritime training institutions aiming to improve safety outcomes and cultivate seafarers who are not only technically proficient but also skilled in teamwork and crisis management, thereby addressing a fundamental need in the global maritime industry.